Pharmacokinetics, metabolism, and toxicity of anisomelic acid and ovatodiolide: Guiding route of administration in preclinical studies - Delshad, Navid; Paul, Preethy; Santos Silva, Michael; Yatkin, Emrah; Voipio, Mikko; Rajendran, Senthil Kumar; Eriksson, John E. (Elsevier B.V., 2026)
Despite extensive progress in cancer therapeutic research, translating promising anticancer compounds into clinical treatments often fails due to suboptimal pharmacokinetic and safety profiles. These shortcomings underscore the critical need for comprehensive pharmacokinetic (PK) analyses in the early stages of drug development. Among the compounds that have shown promising anticancer effects in multiple preclinical studies are anisomelic acid (AA) and ovatodiolide (OVT) — two diterpenoids from plant Anisomeles malabarica. However, their pharmacokinetic and toxicity profile remain poorly characterized. To explore their potential as chemotherapy agents, we first evaluated their key in vitro pharmacokinetic (PK) parameters, followed by an acute oral toxicity assessment and complementary in vivo PK analyses. In vitro experiments showed that both AA and OVT exhibited near-complete solubility in phosphate buffer, high stability, and strong permeability across MDR1-MDCK cell monolayer, and were not substrates of multidrug resistance protein (MDR1). However, OVT underwent rapid metabolism in liver microsomes in the presence of NADPH, whereas AA showed comparatively greater stability under the same conditions. Subsequent in vivo pharmacokinetic (PK) analyses in mice also demonstrated rapid clearance and low systemic bioavailability for both compounds following intravenous (IV) or transdermal (TD) administration. Metabolite identification revealed extensive conjugation to cysteine, and no acute toxicity or mortality was observed at high oral doses. Collectively, these data underscore the distinct metabolic and clearance patterns that limit systemic bioavailability but highlight the favorable safety of AA and OVT. Moreover, while topical administration may offer therapeutic advantages for localized conditions, additional formulation strategies will be crucial to overcome limited bioavailability for systemic use of AA or OVT.